GURU MATA PELAJARAN DAN KONTRIBUSINYA TERHADAP PELAKSANAAN PROGRAM BIMBINGAN KONSELING DIKELAS XI IPA SMA NEGERI 1 MUARO JAMBI - Edrinawati Edrinawati (Universitas Batanghari Jambi, 2018)
The contribution of subject teachers to the implementation of teacher guidance and counselingprogram and education providers in schools is a system, in which each component works together to achieve the instructional and curricular goals. The subject teacher is a co-worker of the teacher guidance and counseling in carrying out his duties at school, because the subject teacher interacts mostly with the students in every students’ activities. Subject teachers have an important role in the implementation of guidance and counseling services. Various cases of learners, especially those related to learning problems, can be assisted and handled by subject teachers.This research was conducted with the aim to see the level of contribution of subject teachers to the implementation of guidance and counseling program in SMA Negeri 1 Muaro Jambi. The research population was the level of contribution of subject teachers to the implementation of guidance and counseling program. In addition, the respondent population was26 subject teachers who teach in XI IPAclass. The questionnaire contained a list of questions that referred to the criteria of guidance and counseling services that were used as data collection. The results reveal that the level of contribution of subject teachers to the implementation of guidance and counseling program in class XI IPA SMA Negeri 1 Muaro Jambi is good that is 80.01%. Keywords: Subject Teachers, Guidance, Counseling